Comparing Ketorolac With Ibuprofen for Postoperative Pain: A Randomized Clinical Trial. Issue 4 (April 2020) - Dwarica, Denicia S.; Pickett, Stephanie D.; Zhao, Yan D.; Nihira, Mikio A.; Quiroz, Lieschen H.
Abstract : Objectives: The objective of this study was to identify differences in pain perception and satisfaction with pain control in women receiving nonsteroidal anti-inflammatory drugs postoperatively. Methods: This was a prospective, randomized controlled trial including urogynecology surgical patients. After surgery, all patients were randomized to receive either intravenous (IV) ketorolac or ibuprofen. The patients completed 3 visual analog scales (VAS) assessing pain at rest, pain with ambulation, and satisfaction with pain control. Postoperative opioid use was also measured. Results: A total of 224 patients (112 in each arm) were included. Pain scores (SD) at rest in all patients who received ketorolac versus those who received ibuprofen was 2.30 (2.1) versus 2.68 (2.34) ( P = 0.20). Pain scores (SD) with ambulation was 3.94 (2.57) versus 4.16 (2.73) ( P = 0.57) in patients who received ketorolac and ibuprofen, respectively. Patients who received ketorolac rated their satisfaction with their pain regimen similarly to those who received ibuprofen ( P = 0.50). The average amount (SD) of hydromorphone used in the ketorolac and ibuprofen arm was 3.68 (4.58) mg and 4.04 (4.97) mg, respectively ( P = 0.58). A subgroup analysis based on type of surgery showed decreased pain at rest (VAS, 2.77 vs 4.88; P = 0.04) and increased satisfaction (VAS, 1.69 vs 4.67; P = 0.003) in patients who had laparotomy and received ketorolac. Conclusions: There was no difference in pain and satisfaction with IV ketorolac compared with IV ibuprofen in patients who underwent all modalities of urogynecologic surgery. A subgroup of patients who underwent laparotomy had less pain with ketorolac.